Diagnosis of imported Ugandan typhoid fever based on local outbreak information: A case report. Issue 11 (November 2016) - Ota, Shinichiro; Maki, Yohei; Mori, Kazuma; Hamamoto, Takaaki; Kurokawa, Atsushi; Ishihara, Masashi; Yamamoto, Takayuki; Imai, Kazuo; Misawa, Kazuhisa; Yuki, Atsushi; Fujikura, Yuji; Maeda, Takuya; et al.
Abstract: Re-emerging multidrug-resistant typhoid fever is becoming a worldwide threat, especially in East Africa. At the beginning of 2015, an outbreak of typhoid fever started in the capital city of Uganda, and 1940 suspected cases were reported by 5 March 2015. In this report, we describe a case of typhoid fever caused by a MDR strain with HIV infection and hemoglobin S-syndrome thalassemia in an Ugandan from Kampala City. It is essential to consider MDR strains of Salmonella enterica serovar Typhi infections, including fluoroquinolone-resistant strains, in patients from Africa and Southeast Asia.